Predicting Gentamicin Induced Nephrotoxicity Using Pharmacometabonomic Approach - Aziz, Fatimatuzzahra’ Abd. (2019)
Gentamicin has been one of the most widely used antibiotics. However, its nephrotoxicity is a major concern as it is filtered through the kidneys for excretion in the form of urine. However, early diagnosis is difficult and no reliable metabolites as biomarkers are currently available. Thus, in this study, a pharmacometabonomic approach using nuclear magnetic resonance (NMR) spectroscopy to investigate the altered metabolic pattern in serum and urine samples prior to administration of gentamicin has been employed to develop a model to predict nephrotoxicity induced by gentamicin and to identify the metabolic biomarkers associated. The aim of this study is therefore to determine the potential of urine and serum metabolites in predicting gentamicin induced nephrotoxicity.